The Influence of Participation in the Student Council (OSIS) on the Study Discipline of Students at SMA Negeri 1 Kroya for the Academic Year 2023/2024 - Nugroho Aziz Mustofa; Elly Hasan Sadeli; Eko Priyanto (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine the extent of the influence of participation in the Student Council (OSIS) on students' study discipline. The method used in this study is an explanatory method with a quantitative approach. The sample used was students of grade XI and XII of SMA Negeri 1 Kroya with a total of 87 students. The data collection technique used questionnaire, observation, and documentation. The data analysis technique used in this study was simple linear regression. Based on the results, the obtained t-value (7.224) was greater than the critical t-value (1.663), and the significance value was less than 0.05 (0.000 0.05), indicating a significant influence of OSIS participation on students' study discipline. The influence of OSIS participation on students' study discipline was 38%, meaning that OSIS participation accounted for 38% of the variation in study discipline, while the remaining 62% could be attributed to other factors or variables not examined in this study. This finding is supported by research results revealing that some students still do not fully adhere to rules or instructions correctly.